P2X7 Receptors as a Therapeutic Target in Cerebrovascular Diseases - Cisneros-Mejorado, Abraham J.; Pérez-Samartín, Alberto; Domercq, María; Arellano, Rogelio O.; Gottlieb, Miroslav; Koch-Nolte, Friedrich; Matute, Carlos (Frontiers in Molecular Neuroscience, 2020)
Shortage of oxygen and nutrients in the brain induces the release of glutamate and ATP that can cause excitotoxicity and contribute to neuronal and glial damage. Our understanding of the mechanisms of ATP release and toxicity in cerebrovascular diseases is incomplete. This review aims at summarizing current knowledge about the participation of key elements in the ATP-mediated deleterious effects in these pathologies. This includes pannexin-1 hemichannels, calcium homeostasis modulator-1 (CalHM1), purinergic P2X7 receptors and other intermediaries of CNS injury downstream of ATP release. Available data together with recent pharmacological developments in purinergic signaling may constitute a new opportunity to translate preclinical findings into more effective therapies in cerebrovascular diseases.